The Role of Positive Emotion in Mediating the Influence of Store Atmosphere on Impulse Buying (A Study on Customers of Uniqlo Outlet at Mall Bali Galeria) - Putu Yuan Barananda; Gede Suparna (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The industry in Indonesia has experienced significant development both online and offline, including the fashion industry, which has also undergone rapid growth. This development inevitably alters consumer behavior toward products in the market. One consumer behavior that requires attention is impulse buying, which refers to unplanned purchases. Impulse buying occurs due to emotional factors, which are also influenced by the store atmosphere, prompting spontaneous purchases. This study aims to examine and analyze the role of positive emotion in mediating the relationship between store atmosphere and impulse buying. The research was conducted among customers of the Uniqlo store at Bali Galeria Mall, with a sample size of 160 respondents selected through purposive sampling. Data collection was carried out using questionnaires. The analytical techniques employed include the Classical Assumption Test, Path Analysis, Sobel Test, and Variance Accounted For (VAF) Test. The analysis results indicate that: Store atmosphere has a positive and significant effect on impulse buying, Store atmosphere has a positive and significant effect on positive emotion, Positive emotion has a positive and significant effect on impulse buying, Positive emotion mediates the effect of store atmosphere on impulse buying. The theoretical implications of this study support previous research findings from the perspective of Consumer Behavior Theory. The practical implications provide guidelines for managers and staff at the Uniqlo store at Bali Galeria Mall to enhance customer impulse buying by leveraging store atmosphere and positive emotion.